Identity and Narration in Chris Marker's La Jetée and the Appearance of the Internet as a Symptom of Cold-War Anxiety - Mansfield, Charlie (Rodopi, Amsterdam and Atlanta, 2001)
CHRIS MARKER'S 29 minute film, La Jetée, first appeared in 1962 in the era of the Cold War, an era which also gave birth to the Internet. The Internet appeared in 1968 as the DARPA network, invented by Paul Baran at Rand Corporation; Baran had been looking at packet-switching since at least 1964 with the idea of building resilience into communications networks (de Rosnay 1995). Taking in turn the three themes of: image, time and narration, this text attempts to show how the building of the Internet and the fears explored in La Jetée have much in common, suggesting that they are both a symptom of the over-arching anxiety of that cold war age which we have inherited and now need to re-analyse today.
Keywords: French; Marker; Identity; Narrative; Film; Mansfield; Internet; Cold War